2018
DOI: 10.1111/jan.13856
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of occupational stress on spirituality and depression of Registered Nurses in tertiary hospital: A structural equation model

Abstract: The stress-moderated model of the influence of spirituality to depression highlights three significant points. First, there is a need to develop individualized, spiritually based interventions based on the spiritual needs of Registered Nurses. Second, policies geared towards positive spirituality in the workplace and spiritual support to nurses must be explored. Finally, nurse managers must identify the sources of occupational stress and implement stress-reducing programmes in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…Spirituality promotes personal faith and reduces stress and depression among nurses. Also, performing religious practices had a protective effect against occupational stress among registered Nurses (Batalla et al, 2019 ). It has been found that religious coping can moderate the effect of stress on outcomes of behavioral disorders and lead to maintenance and protection of communities҆ health against severe crises, such as the COVID-19 pandemic (Pirutinsky et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality promotes personal faith and reduces stress and depression among nurses. Also, performing religious practices had a protective effect against occupational stress among registered Nurses (Batalla et al, 2019 ). It has been found that religious coping can moderate the effect of stress on outcomes of behavioral disorders and lead to maintenance and protection of communities҆ health against severe crises, such as the COVID-19 pandemic (Pirutinsky et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In highly developed countries, i.e., Norway or Canada, the prevalence is 8.8% and 9.1%, respectively. In the studies conducted in the Philippines, it was shown that depression affects one in five nurses (Batalla et al, 2019), while one in four nurses in Brazil (Schmidt et al, 2011), and one in three active nurses and India (Shajan and Nisha, 2019). The studies conducted in Yoon and Kim (2013), in Japan by Furihata et al (2020), and in China by Xie et al (2020) showed that 38.0, 41.7, and 43.83% of nurses, respectively, have depression-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals across the nation report high levels of burnout, depression, and suboptimal health affecting patient safety and healthcare quality (Dyrbye et al, 2017;Jordan, Khubchandani, & Wiblishauser, 2016;Jordan, Nowrouzi-Kia, Gohar, & Nowrouzi, 2015). Nurses have higher rates of substance abuse (Ivey, 2015), are twice as likely to suffer from depression (Batalla et al, 2019;Letvak, Ruhm, & McCoy, 2012;Melnyk et al, 2018), and commit suicide at higher rates (Alderson, Parent-Rocheleau, & Mishara, 2015;Hall, Johnson, Watt, Tsipa, & O'Connor, 2016;Melnyk et al, 2018;Rizzo, 2018) than the national average. In addition, over 50% of nurses report suboptimal physical and mental health (Melnyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%